The Mobility and/or Fixity of Urban and Planning Policies – The Role of Divergent Urban Planning Cultures - Hamedinger, Alexander (European Spatial Research and Policy, 2014)
Cities and regions are increasingly interconnected on a global scale. In the process of the making of cities and regions policy actors increasingly rely on globally flowing and very mobile urban policy models, which have been originally developed in different socio-spatial contexts. Simultaneously the search for these policies and their implementation is refracted by local/regional factors, which are relatively fixed as they are rooted in historically produced planning cultures. In this conceptual paper governance change is discussed through looking at the interplay between fixity and motion in urban development. For this purpose approaches to planning cultures and policy mobilities are related to each other theoretically.